Genomic insights into the role of Salmonella Typhi carriers in antimicrobial resistance and typhoid transmission in Urban Kenya - Susan M. Kavai; Winnie C. Mutai; Cecilia Mbae; Kelvin Kering; Ronald Ng’etich; Peter Muturi; Collins Kigen; Mike Mugo; Diana Imoli; Celestine Wairimu; Samuel Kariuki (PLoS ONE, 2025)
Typhoid fever cases and carriers can transmit Salmonella enterica serovar Typhi (S. Typhi) through fecal shedding. It remains unclear whether the S. Typhi shedding by carriers exhibits similar phenotypic and genotypic characteristics to those from acute cases. We investigated multidrug resistance in S. Typhi from individuals residing in urban informal settlements in Nairobi, Kenya. We recruited participants ≤ 65 years from six health facilities and tested for typhoid infection through blood and stool cultures. The S. Typhi culture-positive cases were treated and followed up after treatment, where index cases and their household contacts provided stool samples for culture. The susceptibility of all S. Typhi isolates was tested against 14 antibiotics using Kirby Bauer disc diffusion. Total deoxyribonucleic acid (DNA) was extracted from selected multi-drug resistant (MDR) S. Typhi for whole genome sequencing using Illumina Nextseq2000, and their genomes were analyzed on Pathogen-watch. Of the 115 S. Typhi isolates, 81/115 (70%) were from cases, while 34/115 (30%) were from carriers. S. Typhi resistance against ampicillin was observed in 32/81 (40%) and 11/34 (32%) of isolates from cases and carriers, respectively, while resistance against co-trimoxazole was observed in 34/81 (42%) and 10/34 (29%) of isolates from cases and carriers, respectively. In addition, resistance against chloramphenicol was observed in 30/81(37%) and 10/34 (29%) in isolates from cases and carriers, respectively. Multidrug resistance was observed in 33% (38/115) of the S. Typhi isolates, with majority, 28/38 (74%) recovered from cases. A subset (22/38, 15 from cases and 7 from carriers) of the MDR isolates was randomly selected for sequencing. All the 22 S. Typhi belonged to genotype 4.3.1, with the majority 15/22 (68%) from genotype 4.3.1.2EA3. All these isolates carried the blaTEM-1D, catA1, dfrA7; sul1, and sul2 AMR genes. GyrA point mutations conferring reduced susceptibility to quinolones and fluoroquinolones were detected in 19/22 (86%) isolates, with the majority 15/22 (79%) occurring on codon 83. This study’s findings highlight the plausibility of typhoid transmission within communities in disease endemic settings. Consequently, the study demonstrates the need for surveillance of antimicrobial resistance, antimicrobial stewardship, deployment of typhoid vaccine and improvement of water, hygiene and sanitation infrastructure in disease endemic settings.